2020
DOI: 10.1088/1755-1315/596/1/012069
|View full text |Cite
|
Sign up to set email alerts
|

Performance of TiO2/Al2O3/carbon nanotube nanocomposite on the photocatalytic degradation of metamifop

Abstract: The photocatalyst of TiO2/Al2O3/CNT nanocomposite was prepared by hydrothermal process. Its performance was evaluated based on the efficiency in degrading metamifop, an active ingredient in the commercial formulation herbicide. The effect of initial concentration metamifop, the dosage of photocatalyst used during photocatalytic degradation of metamifop and the effect of air flow rate were investigated for the evaluation of its performance. The highest percentage degradation of 10 mg/l metamifop obtained from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The results show that after five cycles of the procedure, the 2,4-D removal efficiency has decreased to 96.1% from 98.4% [ 109 ]. In another study, two different photocatalysts which were TiO 2 /Al 2 O 3 /carbon nanotube nanocomposite and TiO 2 /Al 2 O 3 /graphene were utilized for photocatalytic degradation of metamifop where photodegradation percentage were 95% and above in the presence of UV light and 2 Lmin −1 of air [ 110 , 111 ]. Khan et al [ 112 ] found that TiO 2 can efficiently catalyzed the degradation and mineralization of herbicide derivatives chloridazon, and metribuzin in the presence of UV light.…”
Section: Chemical Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that after five cycles of the procedure, the 2,4-D removal efficiency has decreased to 96.1% from 98.4% [ 109 ]. In another study, two different photocatalysts which were TiO 2 /Al 2 O 3 /carbon nanotube nanocomposite and TiO 2 /Al 2 O 3 /graphene were utilized for photocatalytic degradation of metamifop where photodegradation percentage were 95% and above in the presence of UV light and 2 Lmin −1 of air [ 110 , 111 ]. Khan et al [ 112 ] found that TiO 2 can efficiently catalyzed the degradation and mineralization of herbicide derivatives chloridazon, and metribuzin in the presence of UV light.…”
Section: Chemical Treatmentsmentioning
confidence: 99%
“…Y16C Glyphosate 96 hours contact time 400 mgL −1 glyphosate concentration Complete degradation [ 81 ] Randomly methylated cyclodextrin + A. aurescens CTFL7 Trifluralin 19 days contact time 10 mgL −1 trifluralin concentration 88% [ 86 ] Type of Advanced Oxidation Processes (AOPs) UV/H 2 O 2 UV/S 2 O 8 2- UV/HSO 5 − Alachlor UVC lamp, [S 2 O 8 2- ] 0 = [H 2 O 2 ] = 0.3mM, pH = 5.0 UVC lamp, [HSO 5 − ] 0 = 0.3mM, pH = 9.5 Above 95.0% [ 101 ] Fe 0 @Fe 3 O 4 /UV 2,4-D [2,4-D] 0 = 5.0 mgL −1 , [Fe0@Fe3O4] 0 = 0.5 gL −1 , H 2 O 2 = 1 mM, pH = 5.0 ± 0.2, T = 30°C Completely removed in 90 min; nearly 66% of them could be mineralized. [ 107 ] TiO 2 /Al 2 O 3 /carbon nanotube Metamifop 20 mg of TiO2/Al 2 O 3 /CNT photocatalyst, [metamifop] = 10 mgL −1 , air flow rate = 2 Lmin −1 , 3 hours UV irradiation 95.0% [ 111 ] P, K-doped g-C 3 N 4 with cyano group and nitrogen vacancies (PKCN) Atrazine ...…”
Section: Chemical Treatmentsmentioning
confidence: 99%
“…Hence, finding an effective treatment strategy for this type of herbicide is therefore an issue. The majority of techniques have been used, including photocatalytic degradation [5,6], phytoremediation [7], zeolite [8], chemical coagulants [9,10], and various types of absorbents [10,11]. Some of them work well, while others require to be paired with another treatment.…”
Section: Introductionmentioning
confidence: 99%